2018
DOI: 10.1371/journal.pone.0208047
|View full text |Cite
|
Sign up to set email alerts
|

Defining pediatric polypharmacy: A scoping review

Abstract: ObjectivesLack of consensus regarding the semantics and definitions of pediatric polypharmacy challenges researchers and clinicians alike. We conducted a scoping review to describe definitions and terminology of pediatric polypharmacy.MethodsMedline, PubMed, EMBASE, CINAHL, PsycINFO, Cochrane CENTRAL, and the Web of Science Core Collection databases were searched for English language articles with the concepts of “polypharmacy” and “children”. Data were extracted about study characteristics, polypharmacy terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 101 publications
0
62
0
8
Order By: Relevance
“…Two others defined polypharmacy in the general population 3,8 and 1 review, the most recent, focused on paediatric polypharmacy. 9 The studies included in these included reviews were published between 1985 and July 2017.…”
Section: Description Of Included Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two others defined polypharmacy in the general population 3,8 and 1 review, the most recent, focused on paediatric polypharmacy. 9 The studies included in these included reviews were published between 1985 and July 2017.…”
Section: Description Of Included Reviewsmentioning
confidence: 99%
“…15 The last selected review is a scoping review published by an American team in November 2018, including 363 articles. 9 It describes definitions and terminology of paediatric polypharmacy and provides an overview of the wide range of definitions associated to the term "polypharmacy" in paediatric studies. This review's results are similar to those found in other reviews concerning the general population: the vast majority of definitions are quantitative; the difference is the number of medications.…”
Section: Dovepressmentioning
confidence: 99%
“…31,32 This type of assessment is critical to conduct ahead of implementing prescribing policies (eg, restricted formularies or limitations on the number of refills) that could interfere with children's access to essential medications and adversely affect the health of children. 34 This limited our ability to (1) determine if medication switching (eg, cetirizine changed to loratadine) versus add-on therapy contributed to increased CM counts and (2) perform analyses of potential drugdrug interactions. Fourth, chronic conditions and CCCs were identified from claims-based diagnosis codes without validation of actual disease, and these classification systems may have a wide range of sensitivity and specificity across different data sources.…”
Section: Clinical Characteristics By Number Of Cmsmentioning
confidence: 99%
“…5 Yet, there is a paucity of research in this area, with most of the pediatric literature focusing on the outpatient setting and specific populations, including epilepsy and mental health. [6][7][8] How providers, patients, and families translate medication lists to counts of medications-and hence the burden of polypharmacy-is not clearly or consistently described. Often in studies of polypharmacy, researchers utilize medication claims data to count the number of medications a patient has filled from the pharmacy.…”
mentioning
confidence: 99%
“…9 A recent review of the pediatric polypharmacy literature suggested a lower threshold, with any two concurrent medications for at least a day. 7 Yet, the best approach to "count" medications at hospital discharge is unclear. The simplest method is to tally the number of medications listed in the discharge summary.…”
mentioning
confidence: 99%